Lithium iron phosphate battery
By blending silicon-based materials in lithium iron phosphate batteries and optimizing the electrolyte formula, the energy density and fast charging performance of the battery are improved, and the problem of insufficient energy density and fast charging performance of existing lithium iron phosphate batteries is solved, and the improvement is achieved High electric vehicle endurance and battery cycle life.
Patent Information
- Application Number
- CN202411513097.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2024-12-31
AI Technical Summary
The existing lithium iron phosphate batteries have low energy density and fast charging performance, making them difficult to match ternary batteries, especially in terms of range and battery cycle life of electric vehicles.
By blending high-capacity silicon-based materials into the main negative electrode, the average capacity of the negative electrode is increased; small molecule linear solvent is introduced into the solvent of the electrolyte to reduce the density and injection volume of the electrolyte; rationally design the electrolyte formula to improve the Conductivity and wettability ensure stable circulation and thick electrode design of silicon-containing negative electrodes.
The mass energy density of lithium iron phosphate batteries exceeds 200Wh/kg, and the capacity retention rate of 2000 weeks is achieved under 2.2C fast charging conditions, which is greater than or equal to 80%, while improving the fast charging capability and cycle life of the battery.
Smart Images

Figure BDA0005105945150000141 
Figure BDA0005105945150000151 
Figure BDA0005105945150000161
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy technology, and in particular to a lithium iron phosphate battery. Background Art
[0002] Lithium-ion batteries have become the main power source for power batteries. According to the different cathode materials used, lithium-ion batteries are mainly divided into two categories: lithium iron phosphate batteries and ternary batteries. Among them, lithium iron phosphate batteries have become the mainstream products in the market due to their long life, high safety, environmental friendliness, no rare elements and low cost.
[0003] However, compared with ternary batteries, the energy density of lithium iron phosphate batteries is still relatively low (180Wh / kg vs 250Wh / kg), thus limiting the range of electric vehicles. In addition, the kinetic performance of lithium iron phosphate cathode is poor, and the high viscosity and low conductivity of the electrolyte lead to relatively poor fast charging performance.
[0004] In the current commercial lithium iron phosphate batteries, the negative electrode mainly uses graphite, and its theoretical capacity is 372mAh / g, which is relatively low compared to alloy negative electrodes, only 20%-30% of materials such as SiO and SiC, limiting the energy density of the current lithium iron phosphate single cell. At the same time, the current electrolyte system has poor wettability and conductivity, which is not conducive to supporting thick electrode and high-density cell design, and also limits the improvement of cell energy density.
[0005] CN117007337A discloses a high energy density fast-charge lithium iron phosphate battery and its preparation method, including a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte; the positive electrode sheet includes a positive electrode current collector and a positive electrode coating applied on the surface of the positive electrode current collector; the negative electrode sheet includes a negative electrode current collector and a negative electrode coating applied on the surface of the negative electrode current collector; the material of the positive electrode coating includes a positive electrode active substance, a conductive agent, a binder, and a positive electrode solvent; the material of the negative electrode coating includes a negative electrode active substance, a conductive agent, a dispersant, a binder, and deionized water; the positive electrode active substance includes a composite lithium iron phosphate material and a lithium supplement material; the negative electrode active substance includes fast-charge graphite and a silicon-based material. This patent utilizes lithium iron phosphate and lithium supplement materials to provide a higher gram capacity. The lithium supplement material provides additional active lithium. As the amount of silicon negative electrode added increases, the energy density of the battery cell can be further improved. The compounding of fast-charge graphite and silicon-based materials further improves the electrochemical performance of the material. However, this patent increases the energy density of the battery cell by adding lithium to the positive electrode and silicon to the negative electrode at the same time, which greatly increases the cost of the battery cell; in particular, the lithium addition to the positive electrode will produce a large amount of oxygen during the pre-charging and formation process of the battery cell, which requires the battery production line to be modified to achieve this, and the feasibility of practical application is low.
[0006] CN109687014A discloses a high energy density fast-charging lithium-ion power battery, which modifies the positive and negative electrode materials; designs the positive and negative electrode plates as multi-pole ears or full-pole ears with a void structure; designs the conductive agent as a "point-line-surface" conductive network; and improves the diaphragm and electrolyte formulations. The lithium-ion power battery designed in this way has a high energy density and good fast-charging performance. However, this patent only targets the nickel-cobalt-manganese ternary material or the nickel-cobalt-aluminum ternary material system, which has a high energy density, and does not design a solution to increase the energy density of the more mainstream lithium iron phosphate battery.
[0007] CN107959050A can improve the cycle performance, safety performance, service life, energy density and discharge specific capacity of the battery by optimizing the composition of the electrolyte. The electrolyte chamber is obtained by increasing the concentration of lithium salt in the ordinary electrolyte by 1.5 to 2.5 times; the ordinary electrolyte is composed of a sulfone solvent, a linear carbonate solvent and a conductive lithium salt; the conductive lithium salt is a fluorine-containing series lithium salt. However, by increasing the concentration of lithium salt and using a high-viscosity sulfone solvent to improve the cycle performance of the battery, the cost of the electrolyte is greatly increased, and the conductivity of the electrolyte is reduced, and it is impossible to design a fast-charging battery.
[0008] However, simply by optimizing the electrolyte composition, the energy density of lithium iron phosphate batteries is still difficult to exceed 200Wh / kg, which is still a large gap compared with the energy density of ternary batteries (>240Wh / kg).
[0009] Therefore, improving the energy density and fast charging performance of batteries from the perspective of optimizing the design of electrodes and electrolytes is a technical problem that needs to be solved urgently. Summary of the invention
[0010] In view of the above technical problems existing in the prior art, the purpose of the present invention is to provide a lithium iron phosphate battery.
[0011] The lithium iron phosphate battery of the present invention has a mass energy density of >200Wh / kg at a charge and discharge rate of 0.33C and a lithium iron phosphate battery with a 2000-cycle capacity at room temperature under a 2.2C fast charge system (10-80% SOC). The 2000-cycle capacity means that the capacity retention rate after 2000 cycles is greater than or equal to 80%.
[0012] In one embodiment, the lithium iron phosphate battery has a 0.33C charge and discharge cell capacity of >100Ah.
[0013] To achieve the above object, the present invention adopts the following technical solutions:
[0014] In a first aspect, the present invention provides a lithium iron phosphate battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode main material in the positive electrode comprises lithium iron phosphate, and the negative electrode main material in the negative electrode comprises graphite and a silicon-based material;
[0015] The surface density of the positive electrode is ρ1≥23 mg / cm 2 The surface density of the negative electrode is ρ2>7.8mg / cm 2 ;
[0016] The electrolyte includes a lithium salt, a solvent and an additive, wherein the solvent mainly includes ethylene carbonate (EC) and a small molecule linear solvent, the additive includes fluoroethylene carbonate (FEC) and a negative electrode film-forming additive, and the negative electrode film-forming agent includes vinylene carbonate and a lithium salt additive;
[0017] The small molecule linear solvent is: a carboxylic acid ester solvent, an ether solvent or a nitrile solvent with a relative molecular mass ≤90. Taking the total mass of the electrolyte as 100%, the mass fraction of the small molecule linear solvent is 35%-60%, the mass fraction of the fluoroethylene carbonate is M, the mass fraction of the silicon element in the negative electrode layer is W1, 2%≤M≤2×W1, and the mass fraction of the negative electrode film-forming agent is 4%-6%.
[0018] In the present invention, the surface density of the positive electrode is ρ1≥23mg / cm 2 , for example, it can be 23 mg / cm 2 , 24mg / cm 2 , 25mg / cm 2 、26mg / cm 2 , 27mg / cm 2 、28mg / cm 2 , 29mg / cm 2 、30mg / cm 2 wait.
[0019] In the present invention, the surface density of the negative electrode is ρ2≥7.8mg / cm 2 , for example, it can be 7.8 / cm 2 、8.0mg / cm 2 、8.5mg / cm 2 , 9mg / cm 2 、9.5mg / cm 2 、10mg / cm 2 wait.
[0020] In the present invention, the mass fraction of the small molecule linear solvent is 35%-60%, for example, it can be 35%, 37.5%, 40%, 42.5%, 45%, 47.5%, 50%, 52.5%, 55%, 57.5% or 60%, etc.
[0021] In the present invention, the mass fraction W1 of the silicon element in the negative electrode layer satisfies 2%≤M≤10%. As an example, W1 can be 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, etc.
[0022] In the present invention, the mass fraction of the negative electrode film-forming agent is 4.0%-6.0%, for example, 4.0%, 4.2%, 4.5%, 4.8%, 5.0%, 5.2%, 5.5%, 5.8% or 6.0%, etc. If the content of the negative electrode film-forming agent is too high, the room temperature cycle performance will be reduced.
[0023] The present invention improves the energy density and fast charging performance of the battery by optimizing the design of electrodes and electrolytes. The main principles are:
[0024] ① Mixing a certain amount of high-capacity silicon-based materials (such as silicon-carbon materials) into the negative electrode main material increases the average gram capacity of the negative electrode, reduces the mass of the negative electrode material, and thus increases the energy density of the battery.
[0025] ② Introducing a large amount of small molecule linear solvents into the electrolyte solvent can reduce the density and injection volume of the electrolyte, further reduce the weight of the battery cell, and increase the energy density. At the same time, the small molecule linear solvent has a low viscosity and small surface tension, which can improve the wettability of the electrolyte to the electrode. As the wettability is improved, the surface density can be increased (for example, 2mg / cm2 is increased compared to the existing technology). 2 -5mg / cm 2 ) Obtaining a cell design with thick electrodes can increase the proportion of active materials in the cell and further improve the energy density of the battery.
[0026] ③ By rationally designing the electrolyte formula, the electrolyte has high conductivity, low viscosity and good wettability, which can ensure the stable cycle of the silicon-containing negative electrode, so that the battery can adapt to the thick electrode cell design, good fast charging capability and long cycle life. Specifically:
[0027] First, since the expansion of silicon-based negative electrodes is more than 10 times that of graphite negative electrodes, the SEI formed on the surface of silicon-based negative electrodes is easy to rupture, which greatly deteriorates the cycle performance. FEC additives have the dual advantages of forming inorganic LiF and polymer components. In order to ensure that the silicon-doped negative electrode in the present invention has excellent cycle stability, the content of FEC should be controlled within an appropriate range to continuously repair the SEI on the surface of the silicon-doped negative electrode.
[0028] Second, the electrolyte of the present invention has a large content of small molecule linear solvents, which are easily decomposed to produce gas on the surface of the negative electrode. Therefore, by using two functional negative electrode film-forming agents, vinylene carbonate and lithium salt additives, to cooperate and control their total content, it is ensured that the film has high chemical stability and mechanical stability, thereby effectively solving the above-mentioned gas production problem and making the silicon-doped negative electrode circulate stably, ensuring that the battery has an excellent cycle life at room temperature.
[0029] In the present invention, the electrolyte formula design is very critical. If the electrolyte formula design is not met, the technical indicators such as stable cycle of high-silicon negative electrode, high wetting required for thick electrode battery design, and high ionic conductivity required for fast charging cycle cannot be met, and the battery cell is prone to risks such as large-scale gas production and capacity diving during circulation.
[0030] The present invention mainly improves the battery energy density and fast charging performance by increasing the surface density of the positive electrode and mixing silicon material with the negative electrode in combination with a high-conductivity electrolyte, with lower costs and higher application feasibility.
[0031] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0032] As an optimal technical solution of the lithium iron phosphate battery described in the present invention, the negative electrode includes a negative electrode collector and a negative electrode layer arranged on the surface of the negative electrode collector, the positive electrode includes a positive electrode collector and a positive electrode layer arranged on the surface of the positive electrode collector, and the surface density ρ1 of the positive electrode, the surface density ρ2 of the negative electrode, the surface density ρ3 of the positive electrode collector and the surface density ρ4 of the negative electrode collector satisfy the relationship: ρ1 / ρ3+ρ2 / ρ4>7.5.
[0033] In the present invention, the surface density ρ1 of the positive electrode refers to the mass of the positive electrode layer loaded on the positive electrode current collector per unit area. The positive electrode layer includes a positive electrode main material (eg, lithium iron phosphate) and may also include a conductive agent and / or a binder.
[0034] In the present invention, the surface density ρ2 of the negative electrode refers to the mass of the negative electrode layer loaded on the negative electrode current collector per unit area. The negative electrode layer includes a negative electrode main material (eg, graphite and silicon-based materials), and may also include a conductive agent and / or a binder.
[0035] In the present invention, the surface density ρ3 of the positive electrode current collector refers to the mass of the positive electrode current collector per unit area.
[0036] In the present invention, the surface density ρ4 of the negative electrode current collector refers to the mass of the negative electrode current collector per unit area.
[0037] In the present invention, based on the better wettability of the electrolyte, the surface density of the electrode is increased, more active materials are coated on the current collector per unit area, and the mass ratio of active substances (positive and negative electrode materials) to inactive substances (positive and negative electrode current collectors, battery structural parts, etc.) on the monopole sheet is increased to form a thick electrode, thereby reducing the number of battery cell layers and the amount of inactive substances such as copper foil, aluminum foil, and separators, thereby improving the energy density of the battery.
[0038] The present invention does not specifically limit the materials of the positive electrode current collector and the negative electrode current collector. For example, the positive electrode current collector may be aluminum foil, and the negative electrode current collector may be copper foil.
[0039] Preferably, the compaction density of the positive electrode is 2.58 g / cm 3 -2.7g / cm 3 , for example, it can be 2.58 g / cm 3 , 2.59g / cm 3 , 2.60g / cm 3 , 2.61g / cm 3 , 2.62g / cm 3 , 2.63g / cm 3 , 2.64g / cm 3 , 2.65g / cm 3 , 2.66g / cm 3 , 2.67g / cm 3 , 2.68g / cm 3 , 2.69g / cm 3 or 2.70g / cm 3 wait.
[0040] Preferably, the compaction density of the negative electrode is 1.58 g / cm 3 -1.7g / cm 3 , for example, it can be 1.58 g / cm 3 , 1.59g / cm 3 , 1.60g / cm 3 , 1.61g / cm 3 , 1.62g / cm 3 、1.63g / cm 3 , 1.64g / cm 3 , 1.65g / cm 3 、1.66g / cm 3 , 1.67g / cm 3 、1.68g / cm 3 , 1.69g / cm 3 , or 1.70g / cm 3 wait.
[0041] Based on the better wetting ability of the electrolyte in the present invention, the compaction density of the positive electrode and the negative electrode is increased (for example, 0.05 g / cm compared with the prior art). 3 -0.1g / cm 3 ), which can reduce the porosity of the electrode and further improve the energy density of the battery.
[0042] As a preferred technical solution of the lithium iron phosphate battery of the present invention, the small molecule linear solvent is at least one of ethyl acetate, methyl acetate, methyl propionate, ethylene glycol dimethyl ether, acetonitrile or propionitrile.
[0043] Preferably, based on the total mass of the electrolyte as 100%, the mass fraction of the ethylene carbonate is 15%-30%, for example, it can be 15%, 17%, 18%, 20%, 21%, 22%, 24%, 25%, 26%, 27%, 28% or 30%, etc.
[0044] Preferably, the solvent may further include at least one of dimethyl carbonate and / or ethyl methyl carbonate.
[0045] Preferably, the lithium salt includes at least one of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide.
[0046] Preferably, based on the total mass of the electrolyte being 100%, the total mass fraction of the lithium salt is 10%-18%, for example, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17% or 18%.
[0047] Preferably, the lithium salt additive is selected from at least one of lithium difluorooxalatoborate, lithium difluorophosphate, lithium tetrafluoroborate or lithium difluorobisoxalatophosphate.
[0048] Preferably, based on the total mass of the electrolyte as 100%, the mass fraction of the lithium salt additive is 0.5%-1.5%, for example, it can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4% or 1.5%, etc.
[0049] Preferably, the overall conductivity of the electrolyte is ≥14.5 mS / cm.
[0050] Preferably, the mass fraction of silicon element W1 in the negative electrode layer is ≥2%, preferably 2%-10%, and can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% and the like.
[0051] Preferably, the silicon-based material is a silicon-carbon material.
[0052] In the present invention, silicon-carbon material refers to a material that includes both silicon-containing components and carbon materials, wherein the silicon-containing component may be silicon alone, silicon oxide, or both. At the same time, the present invention does not specifically limit the existence form of the silicon-containing component and the carbon material, and the carbon coating layer may cover the silicon-containing component to form a composite, or the two may be dispersed to form a mixture.
[0053] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0054] Compared with the prior art, the present invention has the following beneficial effects:
[0055] (1) The present invention improves the energy density and fast charging performance of the battery by optimizing the design of electrodes and electrolytes. The main principles are:
[0056] ① Mixing a certain amount of high-capacity silicon-based materials (such as silicon-carbon materials) into the negative electrode main material increases the average gram capacity of the negative electrode, reduces the mass of the negative electrode material, and thus increases the energy density of the battery.
[0057] ② Introducing a large amount of small molecule linear solvents into the electrolyte solvent can reduce the density and injection volume of the electrolyte, further reduce the weight of the battery cell and increase the energy density. At the same time, due to the improved wettability of the electrolyte, it is possible to increase the surface density (for example, 2 mg / cm2 more than the existing technology) 2 -5mg / cm 2 ) Obtaining a cell design with thick electrodes can increase the proportion of active materials in the cell and further improve the energy density of the battery.
[0058] ③ By rationally designing the electrolyte formula, the electrolyte has high conductivity, low viscosity and good interface stability, which can ensure the stable circulation of the silicon-containing negative electrode, so that the battery can adapt to the thick electrode cell design as well as good fast charging capability and long cycle life.
[0059] (2) The present invention can increase the mass energy density of lithium iron phosphate batteries from 180-190Wh / kg to more than 200Wh / kg by doping the negative electrode with silicon-based materials, designing thick electrodes, and adjusting the electrolyte formula, thereby further improving the endurance of electric vehicles and improving the fast charging capability. DETAILED DESCRIPTION
[0060] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0061] In the embodiment of the present invention, the main material of the positive electrode in the lithium iron phosphate battery is lithium iron phosphate.
[0062] Example 1
[0063] This embodiment provides a lithium iron phosphate battery, which is composed of a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and a shell, and its manufacturing process is as follows:
[0064] (1) Positive electrode manufacturing: lithium iron phosphate, conductive carbon black, carbon nanotubes, polyvinylidene fluoride and dispersant are mixed in a mass ratio of 96.8:1.0:0.5:1.5:0.2. During the mixing process, N-methylpyrrolidone is used to prepare the mixture into a positive electrode slurry with a solid content of 55%; then the slurry is coated on the aluminum foil current collector respectively, and after drying at 60°C, it is rolled and die-cut to form the required positive electrode sheet, which includes aluminum foil and a positive electrode layer arranged on the surface of the aluminum foil. The surface density ρ1 of the positive electrode is 23 mg / cm 2 The surface density ρ3 of the aluminum foil current collector is 3.6 mg cm -2 (The same below), the compaction density of the positive electrode is 2.58g / cm 3 .
[0065] (2) Negative electrode manufacturing: graphite, silicon carbon material, conductive carbon black, sodium carboxymethyl cellulose, and styrene-butadiene rubber were prepared in a mass ratio of 91.0:5.5:1.2:0.8:1.5, and mixed into a slurry with a solid content of 45% using deionized water as a solvent. The slurry was then coated on a 6-micron thick copper foil current collector, dried at 80°C, and then rolled and die-cut to form the desired negative electrode sheet, which includes a copper foil and a negative electrode layer disposed on the surface of the copper foil. The surface density ρ2 of the negative electrode is 8.67 mg / cm 2 The surface density ρ4 of the copper foil current collector is 5.37 mg cm -2 (The same below), the compaction density of the negative electrode is 1.62g / cm 3 The silicon content in the negative electrode layer is 2.75wt%.
[0066] (3) Electrolyte preparation: The components are mixed and prepared according to the following mass proportions: 14.0 wt% lithium hexafluorophosphate, 25 wt% ethylene carbonate (EC), 10% ethyl methyl carbonate, a small molecule linear solvent (43 wt% ethyl acetate), 4 wt% vinylene carbonate (VC), 3 wt% fluoroethylene carbonate (FEC), 0.5 wt% vinyl sulfate, and 0.5 wt% lithium difluorobis(oxalyl)phosphate.
[0067] (4) Dry cell manufacturing: The positive and negative electrode sheets prepared above are stacked with a ceramic-coated PP separator of corresponding size and thickness of 12 microns using a stacking machine to obtain a coil with a capacity of 120 Ah; after welding the pole ears, they are packaged with aluminum-plastic film, baked at 85°C for 24 hours, and then injected with liquid (the injection amount is 2.8 g / Ah), packaged, and allowed to stand for formation.
[0068] The formation is carried out in a 45°C incubator, and the steps are as follows: 1) Use a current of 0.1C (12A) to charge the battery for 2 hours, and the cut-off voltage is 3.0V; 2) The battery cell is aged in a 45°C incubator for 24 hours, and then taken out, vented, and repackaged; 3) Use a current of 0.2C to charge the battery cell at a constant current and constant voltage to 3.65V, and the cut-off current is 1A; 4) Use a current of 0.2C to discharge the battery cell at a constant current, and the cut-off voltage is 2.0V; 5) Continue to use a current of 1.33A to charge and discharge the battery cell in the range of 2.0V to 3.65V for 2 weeks.
[0069] After the formation is completed, the final sealing is carried out to finally obtain a lithium iron phosphate battery.
[0070] Example 2
[0071] This embodiment provides a lithium iron phosphate battery, and its manufacturing process is basically the same as that of embodiment 1, except for the negative electrode and electrolyte components:
[0072] Negative electrode manufacturing: graphite, silicon carbon material, conductive carbon black, sodium carboxymethyl cellulose, and styrene-butadiene rubber are prepared in a mass ratio of 86.5:10:1.2:0.8:1.5, and deionized water is used as a solvent to mix into a slurry with a solid content of 45%. The slurry is then coated on a copper foil current collector, dried at 80°C, and rolled and die-cut to form the required negative electrode sheet, which includes a copper foil and a negative electrode layer disposed on the surface of the copper foil. The surface density of the negative electrode is 7.9 mg / cm 2 The compaction density of the negative electrode is 1.62g / cm 3 The silicon content in the negative electrode layer is 5wt%.
[0073] (2) Preparation of electrolyte: The components are mixed and prepared according to the following mass proportions: 14.0 wt% lithium hexafluorophosphate, 25 wt% ethylene carbonate (EC), 10% ethyl methyl carbonate, a small molecule linear solvent (40 wt% ethyl acetate), 4 wt% vinylene carbonate (VC), 6 wt% fluoroethylene carbonate (FEC), 0.5 wt% vinyl sulfate, and 0.5 wt% lithium difluorobis(oxalyl)phosphate.
[0074] Example 3
[0075] This embodiment provides a lithium iron phosphate battery, and its manufacturing process is basically the same as that of embodiment 1, except for the negative electrode and electrolyte components:
[0076] (1) In the step of manufacturing the negative electrode, the mass ratio of graphite, silicon carbon material, conductive carbon black, sodium carboxymethyl cellulose, and styrene-butadiene rubber is 81.5:15.0:1.2:0.8:1.5. Deionized water is used as a solvent to mix into a slurry with a solid content of 45%, and then the slurry is coated on a copper foil current collector, and after drying at 80°C, it is rolled and die-cut to form the required negative electrode sheet, which includes a copper foil and a negative electrode layer arranged on the surface of the copper foil. The surface density of the negative electrode is 7.2 mg / cm 2 The compaction density of the negative electrode is 1.62g / cm 3 The silicon content in the negative electrode layer is 10 wt%.
[0077] (2) Preparation of electrolyte: The components are mixed and prepared according to the following mass proportions: 14.0 wt% lithium hexafluorophosphate, 25 wt% ethylene carbonate (EC), 7% ethyl methyl carbonate, a small molecule linear solvent (40 wt% ethyl acetate), 4 wt% vinylene carbonate (VC), 9 wt% fluoroethylene carbonate (FEC), 0.5 wt% vinyl sulfate, and 0.5 wt% lithium difluorobis(oxalyl)phosphate.
[0078] Example 4
[0079] This embodiment provides a lithium iron phosphate battery, and its manufacturing process is basically the same as that of embodiment 1, except that the small molecule linear solvent component in the electrolyte is:
[0080] Electrolyte preparation: The components are mixed and prepared according to the following mass proportions: 14.0wt% lithium hexafluorophosphate, 25wt% ethylene carbonate (EC), 10wt% ethyl methyl carbonate, a small molecule linear solvent (23wt% ethyl acetate, 20wt% methyl acetate), 4wt% vinylene carbonate (VC), 3wt% fluoroethylene carbonate (FEC), 0.5wt% vinyl sulfate, and 0.5wt% lithium difluorobis(oxalyl)phosphate.
[0081] Example 5
[0082] This embodiment provides a lithium iron phosphate battery, and its manufacturing process is basically the same as that of embodiment 1, except that the small molecule linear solvent component in the electrolyte is:
[0083] Electrolyte preparation: The components are mixed and prepared according to the following mass proportions: 14.0wt% lithium hexafluorophosphate, 25wt% ethylene carbonate (EC), 10wt% ethyl methyl carbonate, a small molecule linear solvent (23wt% ethyl acetate, 20wt% ethylene glycol dimethyl ether), 4wt% vinylene carbonate (VC), 3wt% fluoroethylene carbonate (FEC), 0.5wt% vinyl sulfate, and 0.5wt% lithium difluorobis(oxalyl)phosphate.
[0084] Example 6
[0085] This embodiment provides a lithium iron phosphate battery, and its manufacturing process is basically the same as that of embodiment 1, except that the components of the small molecule linear solvent in the electrolyte are as follows:
[0086] Electrolyte preparation: The components are mixed and prepared according to the following mass proportions: 14.0wt% lithium hexafluorophosphate, 25wt% ethylene carbonate (EC), 10wt% ethyl methyl carbonate, 23wt% small molecule linear solvent (ethyl acetate), 20wt% acetonitrile), 4wt% vinylene carbonate (VC), 3wt% fluoroethylene carbonate (FEC), 0.5wt% vinyl sulfate, and 0.5wt% lithium difluorobis(oxalyl)phosphate.
[0087] Example 7
[0088] This embodiment provides a lithium iron phosphate battery, and its manufacturing process is basically the same as that of Example 1, with the only difference being that the total content of VC and lithium salt additives in the electrolyte is adjusted from 4.5% (4% VC + 0.5% lithium salt additive) to 6% (5% VC + 1% lithium salt additive).
[0089] The specific electrolyte solution is: 14.0wt% lithium hexafluorophosphate, 25wt% ethylene carbonate (EC), 8.5% ethyl methyl carbonate, 43wt% small molecule linear solvent (ethyl acetate), 5wt% vinylene carbonate (VC), 3wt% fluoroethylene carbonate (FEC), 0.5wt% vinyl sulfate, and 1wt% lithium difluorobis(oxalyl)phosphate.
[0090] Example 8
[0091] This embodiment provides a lithium iron phosphate battery, and its manufacturing process is basically the same as that of embodiment 1, except that the type of lithium salt additive is changed:
[0092] Electrolyte preparation: The components are mixed and prepared according to the following mass proportions: 14.0wt% lithium hexafluorophosphate, 25wt% ethylene carbonate (EC), 10% ethyl methyl carbonate, 43wt% small molecule linear solvent (ethyl acetate), 4wt% vinylene carbonate (VC), 3wt% fluoroethylene carbonate (FEC), 0.5wt% vinyl sulfate, and 0.5wt% lithium difluorooxalatoborate.
[0093] Comparative Example 1
[0094] The method is basically the same as Example 1, except that a carbonate electrolyte is used.
[0095] The conductivity of carbonate electrolyte is low and the wetting is poor. At the same time, the surface density and compaction density of the positive and negative electrodes need to be reduced, which will cause a decrease in the energy density of the battery cell.
[0096] The manufacturing process is as follows:
[0097] (1) Positive electrode manufacturing: lithium iron phosphate, conductive carbon black, carbon nanotubes, polyvinylidene fluoride and dispersant are mixed in a mass ratio of 96.8:1.0:0.5:1.5:0.2. During the mixing process, N-methylpyrrolidone is used to prepare the mixture into a positive electrode slurry with a solid content of 55%; then the slurry is coated on an aluminum foil current collector, dried at 60°C, and rolled and die-cut to form the required positive electrode sheet. The surface density of the positive electrode is controlled at 20 mg / cm 2 The compaction density of the positive electrode is 2.56 g / cm 3 .
[0098] (2) Negative electrode manufacturing: graphite, silicon carbon material, conductive carbon black, sodium carboxymethyl cellulose, and styrene-butadiene rubber were prepared in a mass ratio of 91.0:5.5:1.2:0.8:1.5, and mixed into a slurry with a solid content of 45% using deionized water as a solvent. The slurry was then coated on a copper foil current collector, dried at 80°C, and then rolled and die-cut to form the desired negative electrode sheet. The surface density of the negative electrode was 7.5 mg / cm 2 The compaction density of the negative electrode is 1.55 g / cm 3 .
[0099] (3) Preparation of electrolyte: A shot of electrolyte is prepared by mixing according to the following mass proportions: 14.5 wt% lithium hexafluorophosphate, 25 wt% ethylene carbonate, 34% ethyl methyl carbonate, 20% dimethyl carbonate, 2.5 wt% vinylene carbonate, 3 wt% fluoroethylene carbonate, 0.5 wt% vinyl sulfate, and 0.5 wt% lithium difluorooxalatoborate.
[0100] Comparative Example 2
[0101] The method is basically the same as Example 1, except that the amount of FEC in the electrolyte is 1.5 wt %.
[0102] Electrolyte preparation: The components are mixed and prepared according to the following mass proportions: 14.0wt% lithium hexafluorophosphate, 25wt% ethylene carbonate (EC), 10% ethyl methyl carbonate, 44.5wt% small molecule linear solvent (ethyl acetate), 4wt% vinylene carbonate (VC), 1.5wt% fluoroethylene carbonate (FEC), 0.5wt% vinyl sulfate, and 0.5wt% lithium difluorobis(oxalyl)phosphate.
[0103] Comparative Example 3
[0104] The method is basically the same as Example 1, except that the lithium salt additive lithium difluorobis(oxalyl)phosphate is not used in the electrolyte, and the content of vinyl sulfate is adjusted from 0.5wt% to 1.0wt%.
[0105] Electrolyte preparation: The components are mixed and prepared according to the following mass ratio: 14.0wt% lithium hexafluorophosphate, 25wt% ethylene carbonate (EC), 10wt% ethyl methyl carbonate, 43wt% small molecule linear solvent (ethyl acetate), 4wt% vinylene carbonate (VC), 3wt% fluoroethylene carbonate (FEC), and 1.0wt% vinyl sulfate.
[0106] Comparative Example 4
[0107] The method is basically the same as Example 2, except that less vinylene carbonate and lithium salt additives are used in the electrolyte, and the content of ethyl methyl carbonate is adjusted from 10wt% to 11.8wt%.
[0108] Electrolyte preparation: The components are mixed and prepared according to the following mass proportions: 14.0wt% lithium hexafluorophosphate, 25wt% ethylene carbonate (EC), 11.8wt% ethyl methyl carbonate, 43wt% small molecule linear solvent (ethyl acetate), 2.5wt% vinylene carbonate (VC), 3wt% fluoroethylene carbonate (FEC), 0.5wt% vinyl sulfate, and 0.2wt% lithium difluorobis(oxalyl)phosphate.
[0109] Comparative Example 5
[0110] The method is basically the same as Example 2, except that an excessive amount of small molecule linear solvent is used in the electrolyte and the contents of EC and ethyl methyl carbonate are reduced.
[0111] Electrolyte preparation: The components are mixed and prepared according to the following mass proportions: 14.0wt% lithium hexafluorophosphate, 12wt% ethylene carbonate (EC), 5% ethyl methyl carbonate, 61wt% small molecule linear solvent (ethyl acetate), 4wt% vinylene carbonate (VC), 3wt% fluoroethylene carbonate (FEC), 0.5wt% vinyl sulfate, and 0.5wt% lithium difluorobis(oxalyl)phosphate.
[0112] Table 1 below provides the characteristic relationship between each embodiment and the comparative example in the present invention, wherein the contents are all mass fractions, based on the total mass of the electrolyte, W1 is the mass fraction of the silicon element in the negative electrode layer, M is the mass fraction of fluoroethylene carbonate, and VC is vinylene carbonate:
[0113] Table 1
[0114]
[0115]
[0116] To facilitate the performance differences between the embodiments and the comparative examples, the following three tests were conducted, and the test results of the embodiments and the comparative examples are provided in Table 2.
[0117] (I) Calculation of energy density of battery cells:
[0118] At 25°C, the cells of the above schemes are charged to 3.65V at a constant current of 0.33C, and then discharged to 1.5V at a constant current of 0.33C, and the rated discharge capacity and rated discharge voltage of the cells can be obtained. Then, by weighing the mass of the cells, the mass energy density of the cells can be calculated, and the energy density of the cells = cell capacity × rated discharge voltage / total mass of the cells.
[0119] (II) Normal temperature cycle test:
[0120] At 25°C and 45°C, the battery cells manufactured in the above embodiments and comparative examples were charged at 0.2C current in the 0-10% SOC range, then fast charged at an average current of 2.2C in the 10-80% SOC range, and finally charged at a low current of 0.2C to 3.65V. After the battery cell is fully charged, it is left to stand for 10 minutes, and then discharged at a constant current of 1C to 2.0V. This cycle is repeated until the capacity retention rate of the battery cell is less than 80%, and the number of cycles is counted.
[0121] (III) High temperature storage test:
[0122] First, the battery was charged and discharged three times at 0.5C / 0.5C (3.65V~2.5V) at room temperature, and then the fully charged (DOD=100SOC%) battery was stored in a 55℃ oven for 30 days. After being taken out, it was allowed to stand at room temperature for 4 hours, and then discharged at 0.5C at room temperature. Then, it was charged and discharged three times, and the last discharge capacity was recorded as the recoverable capacity. The ratio of the recoverable capacity to the initial discharge capacity was the capacity recovery rate of 55℃ high-temperature storage for 30 days.
[0123] Table 2
[0124]
[0125] Combined with the analysis in Table 2, the present invention adopts thick electrodes and high compaction design for both the positive and negative electrodes of the battery cell, with low porosity, low electrolyte density and small injection volume, so that the energy density of the battery cell can exceed 200Wh / kg, and the capacity retention rate is greater than or equal to 80% at room temperature for 2000 weeks under the 2.2C fast charging system, and the capacity recovery rate is greater than or equal to 95% after 30 days of high-temperature storage at 55°C.
[0126] Compared with Example 1, the negative electrode of Example 2 is mixed with more high-capacity silicon-based materials, which can support the energy density of the battery cell to reach 205Wh / kg.
[0127] Compared with Example 1, Comparative Example 1 uses a carbonate electrolyte, which has relatively poor wetting ability, so it is necessary to reduce the surface density and compaction density of the positive and negative electrodes to ensure that the battery cell has good cycle capacity and meets the 2000-cycle cycle index at room temperature. However, the energy density of the battery cell can only meet 194Wh / kg.
[0128] Compared with Example 2, the FEC content in the electrolyte of Comparative Example 2 is only 1.5wt%, which does not meet the requirement of ≥2wt%, and cannot make the negative electrode mixed with silicon cycle stably, and cannot meet the project's indicator of 2000 cycles at room temperature. This shows that in a high silicon content system, it is very important to use a reasonable amount of FEC.
[0129] Compared with Example 2, the electrolyte in Comparative Example 3 does not use lithium salt additives, and cannot meet the SOR index of 2000 cycles at room temperature, indicating that inorganic lithium salt additives are essential for achieving good cycle performance.
[0130] Compared with Example 2, the amount of VC and lithium salt additives in the electrolyte of Comparative Example 4 is insufficient to meet the SOR index of 2000 cycles at room temperature. This shows that the appropriate amount of negative electrode film-forming additives is crucial to achieve good cycle performance.
[0131] Compared with Example 2, in Comparative Example 5, due to the use of excessive small molecule linear solvent (>60%) and low EC content, the conductivity of the electrolyte decreased, which deteriorated the cycle performance and high temperature calendar life of the battery.
[0132] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A lithium iron phosphate battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode main material in the positive electrode comprises lithium iron phosphate, characterized in that: The negative electrode main material in the negative electrode includes graphite and silicon-based materials; The surface density of the positive electrode is ρ1≥23 mg / cm 2 The surface density of the negative electrode is ρ2≥7.8mg / cm 2 ; The electrolyte includes lithium salt, solvent and additive, the solvent mainly includes vinyl carbonate and small molecule linear solvent, the additive includes fluoroethylene carbonate and negative electrode film-forming additive, the negative electrode film-forming agent includes vinylene carbonate and lithium salt additive; the small molecule linear solvent is: carboxylic acid ester solvent, ether solvent or nitrile solvent with a relative molecular mass ≤90; based on the total mass of the electrolyte as 100%, the mass fraction of the small molecule linear solvent is 35%-60%, the mass fraction of the fluoroethylene carbonate is M, the mass fraction of the silicon element in the negative electrode layer is W1, 2%≤M≤2×W1, and the mass fraction of the negative electrode film-forming agent is 4%-6%.
2. The lithium iron phosphate battery according to claim 1, characterized in that: The negative electrode includes a negative electrode collector and a negative electrode layer arranged on the surface of the negative electrode collector, the positive electrode includes a positive electrode collector and a positive electrode layer arranged on the surface of the positive electrode collector, and the surface density ρ1 of the positive electrode, the surface density ρ2 of the negative electrode, the surface density ρ3 of the positive electrode collector and the surface density ρ4 of the negative electrode collector satisfy the relationship: ρ1 / ρ3+ρ2 / ρ4>7.
5.
3. The lithium iron phosphate battery according to claim 1 or 2, characterized in that: The compaction density of the positive electrode is 2.58 g / cm 3 -2.7g / cm 3 ; Preferably, the compaction density of the negative electrode is 1.55 g / cm 3 -1.7g / cm 3 .
4. The lithium iron phosphate battery according to any one of claims 1 to 3, characterized in that: The small molecule linear solvent is at least one of ethyl acetate, methyl acetate, methyl propionate, ethylene glycol dimethyl ether, acetonitrile or propionitrile.
5. The lithium iron phosphate battery according to any one of claims 1 to 4, characterized in that: Based on the total mass of the electrolyte being 100%, the mass fraction of the ethylene carbonate is 15%-30%.
6. The lithium iron phosphate battery according to any one of claims 1 to 5, characterized in that: The solvent also includes at least one of dimethyl carbonate and / or ethyl methyl carbonate.
7. The lithium iron phosphate battery according to any one of claims 1 to 6, characterized in that: In the electrolyte, the lithium salt includes at least one of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide; Preferably, based on the total mass of the electrolyte being 100%, the total mass fraction of the lithium salt is 10%-18%.
8. The lithium iron phosphate battery according to any one of claims 1 to 7, characterized in that: The lithium salt additive is selected from at least one of lithium difluorooxalatoborate, lithium difluorophosphate, lithium tetrafluoroborate or lithium difluorobisoxalatophosphate; Preferably, based on the total mass of the electrolyte being 100%, the mass fraction of the lithium salt additive is 0.5%-1.5%.
9. The lithium iron phosphate battery according to any one of claims 1 to 8, characterized in that: The overall conductivity of the electrolyte is ≥14.5 mS / cm.
10. The lithium iron phosphate battery according to any one of claims 1 to 9, characterized in that: The mass fraction of silicon in the negative electrode layer W1 is ≥ 2%, preferably 2%-10%; Preferably, the silicon-based material is a silicon-carbon material.
Citation Information
Patent Citations
Sulfuryl electrolyte for high-energy-density and high-safety lithium ion battery and preparation method of Sulfuryl electrolyte
CN107959050A
High energy density fast charging type lithium ion power battery
CN109687014A
Tire recycling detection device
CN117007337A
Electrolyte, preparation method thereof, high-energy-density lithium ion battery containing electrolyte and preparation method thereof
CN111769327A
Lithium ion battery
CN114204109A
Cited By
Electrolyte and preparation method thereof, lithium battery and electric device
CN120527469A
Battery monomer, battery device and electric equipment
CN122436566A
Electrolyte and preparation method therefor, lithium battery and electric device
EP4769629A1
Electrolyte and preparation method therefor, lithium battery and electric device
WO2026081723A1
Lithium iron phosphate battery
WO2026092217A1
